A Pedagogical Guide to Teaching an Interpersonal Communication Course - Jordan Atkinson; David McMahan (Central States Communication Association, 2019)
This forum article focuses on the instruction of an interpersonal communication course. Interpersonal communication courses are widely included in undergraduate communication curriculum and can be fundamental to student development. The authors provide foundational material and various content areas generally included in such a course. The authors also provide various applied assignments and issues to consider when teaching an interpersonal communication course.